2010
DOI: 10.1111/j.1747-4949.2010.00462.x
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Retinal, Neuroimaging and Ultrasonographic Markers of Lacunar Infarcts

Abstract: The association of retinal microangiopathy (but not vascular retinopathy) and leukoaraiosis is linked to small-vessel disease and may be a useful marker of lacunar infarcts not secondary to a macrovascular lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
(57 reference statements)
1
9
0
Order By: Relevance
“…Neuroimaging and ultrasonographic evaluation was done at admission. A detailed description of the neurological examination protocol was published elsewhere . In summary, LI was diagnosed when the patient had one of the clinical lacunar syndromes lasting > 24 hours, no evidence of cortical dysfunction, and a normal or deep focal infarction with a diameter ≤15 mm in an appropriate location visualized by CT/MRI.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroimaging and ultrasonographic evaluation was done at admission. A detailed description of the neurological examination protocol was published elsewhere . In summary, LI was diagnosed when the patient had one of the clinical lacunar syndromes lasting > 24 hours, no evidence of cortical dysfunction, and a normal or deep focal infarction with a diameter ≤15 mm in an appropriate location visualized by CT/MRI.…”
Section: Methodsmentioning
confidence: 99%
“…A detailed description of the neurological examination protocol was published elsewhere. 24,31 In summary, LI was diagnosed when the patient had one of the clinical lacunar syndromes lasting > 24 hours, no evidence of cortical dysfunction, and a normal or deep focal infarction with a diameter ≤15 mm in an appropriate location visualized by CT/MRI. The presence of an LI in the baseline CT in which the topography did not correspond with the present clinical syndrome was considered a silent infarct (i.e., asymptomatic brain infarcts).…”
Section: Neurological Examinationmentioning
confidence: 99%
“…An increase in PI is associated with white matter hyperintensities and lacunar infarction, especially in diabetic patients. A strong relationship between retinal microangiopathy and PI with neuroimaging markers of brain small vessel disease was demonstrated in a previous study [18]. It has been speculated that the thickened fibrotic wall of small vessel microangiopathy loses its elastic properties and becomes rigid.…”
Section: Discussionmentioning
confidence: 93%
“…Recently, it has also been suggested that an increased plasma total homocysteine level was independently associated with increased PIs of intracranial arteries [17]. Several previous studies have demonstrated that the PI is an index of the presence and severity of diffuse small vessel disease [8,9,18]. An increase in PI is associated with white matter hyperintensities and lacunar infarction, especially in diabetic patients.…”
Section: Discussionmentioning
confidence: 98%
“…The same explorer (SA), blinded to clinical data, performed the ultrasonographic study using high‐resolution B‐mode ultrasound (Aplio 50 [Toshiba aplio 50, MCM1754TSA, Rome, Italy] Toshiba SSA‐700 [Toshiba Medical Systems Corporation, Otawara‐SHI, Japan]) with a 7.5 MHz, linear‐array transducer (Linear array transducer PLT‐704AT, Toshiba, Tochigi, Japan; Phased array transducer PST‐20CT, Toshiba, Tochigi, Japan) (Rodríguez et al., ). In brief, the image was focused on the posterior (far) wall of the left carotid artery.…”
Section: Methodsmentioning
confidence: 99%